The Pathological Mechanisms of Estrogen-Induced Cholestasis: Current Perspectives - Zu, Yue; Yang, Jinyu; Zhang, Chengliang; Liu, Dong (Frontiers in Pharmacology, 2021)
Estrogens are steroid hormones with a wide range of biological activities. The excess of estrogens can lead to decreased bile flow, toxic bile acid (BA) accumulation, subsequently causing intrahepatic cholestasis. Estrogen-induced cholestasis (EIC) may have increased incidence during pregnancy, and within women taking oral contraception and postmenopausal hormone replacement therapy, and result in liver injury, preterm birth, meconium-stained amniotic fluid, and intrauterine fetal death in pregnant women. The main pathogenic mechanisms of EIC may include deregulation of BA synthetic or metabolic enzymes, and BA transporters. In addition, impaired cell membrane fluidity, inflammatory responses and change of hepatocyte tight junctions are also involved in the pathogenesis of EIC. In this article, we review the role of estrogens in intrahepatic cholestasis, and outlined the mechanisms of EIC, providing a greater understanding of this disease.